The health of education workers: Situations of vulnerability and illness - Lazaroto , Neusa Vicente; Aires, Marinês (Seven Editora, 2024)
The present study has as objective: to identify studies on the health of the education worker and situations of vulnerability and illness experienced in everyday school life during and after the covid 19 pandemic . In addition, it also seeks to problematize and discuss issues related to teacher health promotion in the school context, from the perspective of building public policies which focus on teacher health. For this, the reference used was of health policies, National Policy for Health Promotion and Education and the Welfare, Health and Quality of Life Policy at Work and Valorization of Education Professionals. Methodology: This is a qualitative study of the construction of the state of knowledge carried out in the databases of the Catalog of Theses and Dissertations of the Coordination for the improvement of Higher Education Personnel and the Brazilian Digital Library of Theses and Dissertations. Results: The results indicate that the overload of work hours, external demands, stress, little mastery of technological tools, psychological shocks and lack of interaction with colleagues imposed by the pandemic context impact the physical, mental and psychological well-being of the teacher, leading to the development of anxiety and burnout syndrome. The research contributes to highlight factors that lead teachers to illness, making them vulnerable when facing these results. It is necessary to plan actions to improve the quality of life and promotion of health and well-being of these professionals. DOI:https://doi.org/10.56238/sevened2024.009-025